Staple Food Consumption Patterns of Arfak Tribe Farmer Households in Warmare District - Ryvany Dampa; Obadja A. Fenetiruma; Agtha W. Widati (MultiTech Publisher, 2024)
This research was conducted in Warmare District, with the aim of examining the staple food consumption patterns of Arfak Tribe farming households in Warmare District. This research uses a quantitative approach using survey methods. The method used to collect data in this research was 24 hour recall. The research population is Arfak tribe farming households who cultivate tubers and rice fields in the Warmare District, namely Kwau Village, Guentuy Village and Indisey VillageThe results of the research show that the average staple food consumption pattern in Kwau Village is the highest in the sweet potato food type, namely 1,595.54 grams per day, Guentuy Village and Indisey Village, on average, the type of food most consumed is grains (white rice). 1,486.37 grams per day and 1,451.83 grams per dayThe average expected food pattern score for tuber foods, namely sweet potatoes, taro and cassava, has reached the normative expected food pattern score, for the grains group, Kwau Village has not yet reached the expected and normative food pattern score, while for Guentuy Village and Indisey Village it has achieve normative expected food pattern scores.